1991
DOI: 10.1177/144078339102700202
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Mobility in Segmented Labour Markets: The Experience of Immigrant Workers in Melbourne

Abstract: This paper presents the results of a survey of a sample of Greek, Yugoslav and Vietnamese born persons who have worked in manufacturing in Melbourne. Despite individual differences in training and experience before arriving in Australia and differences in their time of arrival, almost all the men and women first obtained jobs here as operators, labourers or drivers. There is evidence about the informal processes that channel migrants into such jobs. But once in these jobs, mobility is very low: about one half … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Labour market segmentation theorists provide us with a broad model of the stratified structure of labour market arrangements and useful insights into the formal and informal processes shaping labour market outcomes (Alcorso 2003;Campbell et al 1991;Craig et al 1985;Doeringer and Piore 1971;Gordon et al 1982;Groutsis 2006;Herod 2003;Ho and Alcorso 2004;Massey 1997;Peck 1996;Sassen 1998;Vietorisz and Harrison 1973). However, they do not capture the norms within and between groups (employers, recruiters and employees), giving rise to the segmented outcomes (Halpern 2005).…”
Section: Theoretical Backgroundmentioning
confidence: 98%
“…Labour market segmentation theorists provide us with a broad model of the stratified structure of labour market arrangements and useful insights into the formal and informal processes shaping labour market outcomes (Alcorso 2003;Campbell et al 1991;Craig et al 1985;Doeringer and Piore 1971;Gordon et al 1982;Groutsis 2006;Herod 2003;Ho and Alcorso 2004;Massey 1997;Peck 1996;Sassen 1998;Vietorisz and Harrison 1973). However, they do not capture the norms within and between groups (employers, recruiters and employees), giving rise to the segmented outcomes (Halpern 2005).…”
Section: Theoretical Backgroundmentioning
confidence: 98%
“…This hypothesis has been tested by a number of scholars. For example, Campbell et al (1991) concluded that the initial allocation of immigrants in Australia to low skilled jobs in manufacturing has a long-term significance for their careers, rather than being a phenomenon of transition. Studies in the Netherlands have also shown that immigrants tend to improve their occupational status with the duration of residence in the new country but do not catch up to the native population, and argue that differences in occupational adjustment can be explained by a lack of country-specific knowledge and language (Zorlu 2011).…”
Section: Theory and Previous Studiesmentioning
confidence: 99%
“…The labour market performance of immigrants from different immigration entry categories has only recently been examined (Miller 1986;Wooden and Robertson 1989;Jones and McAllister 1991;Wooden 1991;Iredale and D' Arcy 1992). While the experience of Vietnamese has received the greatest attention (Coughlan 1989(Coughlan , 1991Tran and Hollon 1991;Viviani, Coughlan and Rowland 1993), there are relatively few recent studies which focus on specific and/or the smaller birthplace groups from these refugee source countries (Campbell, Fincher and Webber 1991;Jones and McAllister 1991;Iredale and D' Arcy 1992;and Stromback, Chapman, Dawkins and Bushe-Jones 1992). The experience of Cambodians has received little attention, with the exception of the work of Stevens (1984, I993a) and their peripheral inclusion in the analysis of Coughlan (1991).…”
Section: Introductionmentioning
confidence: 99%
“…This was considered to be related to the entry of Australian educated persons into the labour force rather than upward mobility. Tran and Holton (1991) and Campbell et a!. (1991) found limited evidence of upward mobility, although there were indications that there was some improvement in job status by individuals over time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation